Characterization of Ralstonia solanacearum race 2 biovar 1 associated with moko disease of banana in Peninsular Malaysia - Mohamed Zulperi, Dzarifah (2015)
Moko disease caused by Ralstonia solanacearum race 2 biovar 1 (R. solanacearum R2Bv1) is a major disease affecting banana (Musa spp.) production. Although local reports suggested that this disease is widespreading in Malaysia, characterization of R. solanacearum strains associated with Moko disease in this country has not been done. This study was conducted to isolate, identify and characterize R. solanacearum R2Bv1 of Moko-causing strains in Peninsular Malaysia. During March 2011 to June 2012, 170 banana plants associated with Moko disease and adjacent soil samples were collected in 12 different locations of five outbreak states in Peninsular Malaysia comprising Kedah, Selangor, Pahang, Negeri Sembilan and Johor with disease incidence exceeding 80 % in some severely affected plantations. All 197 isolates produced fluidal colonies that were white to pink coloration after incubation at 24 to 48 hours at 29 °C on Kelman‘s TZC agar medium and were divided into two defined colony type, the B and SFR types. These isolates appeared as Gram-negative rods after Gram-stain, and positive for potassium hydroxide (KOH), Kovacs oxidase, catalase and lipase activity on Tween 80 solution tests. In biovar determination, only 30 isolates displayed characteristics of biovar 1 R. solanacearum, which was negative for utilization of disaccharides and hexose alcohols. Tobacco hypersensitivity assay revealed all isolates elicited hypersensitive response (HR) at 12 h after infiltration, suggesting that they were of race 2. In preliminary pathogenicity study, all 30 isolates were virulence towards three Moko most affected local banana cultivars namely Musa paradisiaca cv. Nipah, Musa paradisiaca cv. Tanduk and Musa acuminata cv. Berangan cultivars with diverse degrees of virulence; highly virulent, moderately virulent and weakly virulent with isolate NS-N1 as the most virulent, while isolates Ked-KN4 and Ked-KN5 were classified as weakly virulent. Musa paradisiaca cv. Nipah (ABB triploid) significantly exhibited the highest degree of severity to R. solanacearum, followed by Musa paradisiaca cv. Tanduk (AAB triploid) and Musa acuminata cv. Berangan (AAA triploid). Moreover, statistical results revealed there were relationships between geographical origins of isolates and their severity, with the most and the lowest severity was related to isolates from Johor and Negeri Sembilan. This study represents the first evidence on the introduction of R. solanacearum biovar 1 associated with Moko disease of banana in Peninsular Malaysia. Partial 16S rDNA sequence analyses disclosed that all 30 isolates of R. solanacearum biovar 1 were clustered to the published R. solanacearum biovar 1 related to Moko-causing strains from the Philippines (MOD5 and R633) with 91 % Bayesian posterior probability support and completely different from Ralstonia syzygii (R. syzygii, S444E), blood disease bacterium (T520) and the outgroup strain, Xanthomonas spp. (55485). Meanwhile, phylogenetic analyses further demonstrated that all strains were grouped with 100% posterior probability support to the published R. solanacearum race 2 insertion sequence gene, ISRso19 (AF450275). Phylotype-specific multiplex PCR (Pmx-PCR) showed all strains belonged to phylotype II displaying a 372 bp amplicon. Phylogenetic analyses of endoglucanase (egl) sequences clustered all 30 strains into phylotype II/4, together with the reference sequences strains from Peru (UW129, UW162 and UW163) and Colombia (UW070). Bioinformatics analysis of pooled rep-PCR fingerprinting method defined two major groups; cluster 1 (sub-group A and B) and cluster 2 (sub-group C), with 35 % average similarity coefficient within these two clusters. The sub-groups in cluster 1 were represented by strains from Kedah, Selangor, Negeri Sembilan and Johor; while cluster 2 sub-group was represented exclusively by strains of Pahang. This is indeed the first time that genetic diversity of R. solanacearum R2Bv1 has been characterized in this country, where rep-PCR technique clearly distinguished clonal lineages of Moko-causing strains in Peninsular Malaysia. These findings provide constructive documentations on R. solanacearum R2Bv1 in Malaysia, since banana has been identified as the second most important commercial fruit crop with a high economic value in this country.